THE IMPACT OF TELEVISION ADVERTISING ON YOUNG CONSUMERS - Agnieszka Anna Siedlecka; Klaudia Juszczuk; Wioleta Kuflewska (Rozprawy Społeczne)
Abstract One of the large-scale marketing tools is TV advertising. The aim of the article is to analyze the impact and perception of television advertising by young consumers.